Membandingkan Metode SAW Dan MFEP Dalam Penentuan Jurusan di Tingkat SLTA - Rini Sovia; Aulia Fitrul Hadi (Ikatan Ahli Informatika Indonesia (IAII), 2019)
SMAN 10 Padang is one of the leading schools in the city of Padang State School which has two majors, namely Science (Science Knowledge) and Social Sciences (Social Sciences). A distinctive feature of this school is one of the international standard pilot schools (RSBI) by implementing bilingual and accelerating classes. On average students lack understanding in the selection of majors according to their abilities. Many people fail in the way they have found. To facilitate the determination of majors, a Decision Making System (SPK) is needed to find criteria. In SPK there are several methods in searching criteria, which are usually used by SAW with MFED. Based on the research carried out, by comparing the two methods, the data are grouped into three criteria, namely the value of the Natural Sciences National Examination, Psychology tests, and Interests. The results of this study show about MFEP method take a high accuration between SAW. An accuration of SAW have 38.3 % and MFEP have 70.5%.